Simultaneous online monitoring of viscosity and oxygen transfer rate in shake flask cultures - René Hanke; Michaela Sieben; Maurice Finger; Kilian Schnoor; Simon Jeßberger; Julia Weyand; Lluìs Coloma de la Fuente; Marcel Mann; Amizon Azizan; Udo Kosfeld; Jochen Büchs (Journal of Biological Engineering)
Abstract Shake flasks are among the most relevant culture vessels for early-stage process development of viscous microbial cultures. While online process monitoring systems are available for temperature, pH, biomass concentration, dissolved oxygen tension and respiration activity, online measuring techniques for viscosity are not yet commercially available. Especially during the production of biopolymers and the cultivation of filamentous fungi or bacteria, quantification of fermentation broth viscosity is essential to ensure adequate mixing as well as gas/liquid mass and heat transfer. In this work, a previously developed quantitative online viscosity measurement technique, termed ViMOS, is refined to monitor the apparent viscosity of up to eight shake flask cultures in parallel. In addition, the necessary preparation to ensure reproducible measurements is elucidated. By cultivating the two exopolysaccharide forming bacterial strains, Paenibacillus polymyxa and Xanthomonas campestris, as well as the filamentous fungus Trichoderma reesei, the ViMOS was successfully validated for viscosity values up to 120 mPa·s. The combination with oxygen transfer rate monitoring via a RAMOS device allowed to detect microbial growth phases, oxygen limitations, biopolymer production and degradation, as well as the morphological development of filamentous cultures. This dual online monitoring has the potential to improve screening conditions and simplify scale-up procedures of small-scale bioprocesses.